2015
DOI: 10.1111/cns.12387
|View full text |Cite
|
Sign up to set email alerts
|

Function of Nogo‐A/Nogo‐A Receptor in Alzheimer's Disease

Abstract: Nogo-A is a protein inhibiting axonal regeneration, which is considered a major obstacle to nerve regeneration after injury in mammals. Rapid progress has been achieved in new physiopathological function of Nogo-A in Alzheimer's disease in the past decade. Recent research shows that through binding to Nogo-A receptor, Nogo-A plays an important role in Alzheimer's disease (AD) pathogenesis. Particularly, Nogo-A/Nogo-A receptors modulate the generation of amyloid β-protein (Aβ), which is thought to be a major ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 97 publications
(112 reference statements)
0
15
0
Order By: Relevance
“…It has been reported that NgR1 can bind to amyloid precursor protein (APP), and investigation of human brain samples found that NgR1 may be concentrated in amyloid plaques (Park et al, 2006a). Another study showed that NgR1 may remove amyloid beta protein (Aβ) from the brain and improve spatial memory in a transgenic mouse model, suggesting that the central Aβ residues may bind to the surface of NgR1 (Park et al, 2006b;Xu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that NgR1 can bind to amyloid precursor protein (APP), and investigation of human brain samples found that NgR1 may be concentrated in amyloid plaques (Park et al, 2006a). Another study showed that NgR1 may remove amyloid beta protein (Aβ) from the brain and improve spatial memory in a transgenic mouse model, suggesting that the central Aβ residues may bind to the surface of NgR1 (Park et al, 2006b;Xu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The Rho/ROCK pathway is downstream of NogoA/NgR. It is involved in the progression of AD via regulation of APP metabolism, Aβ generation, reduction of phosphorylated tau levels and inhibition of neuronal regeneration (Xu et al, 2015). Consistent with the previous observation, it was found here that Fasudil treatment reduces both the expression of ROCK2 and the ratio of p-ROCK2/ROCK2 in the brain of APP/PS1 transgenic mice, which is also consistent with the presence of increased synaptophysin and Gap43.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study found that the deletion of the Nogo gene improves learning and memory deficits in APP transgenic mice and restores the levels of some synaptic markers, including synaptophysin and Gap43 (Masliah et al, 2010). Furthermore, it has been suggested that Nogo-A may trigger the occurrence and development of AD by affecting Aβ metabolism and inhibiting synaptic plasticity (Xu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NogoA, a myelin-rich membrane protein, is a potent neurite outgrowth inhibitor and noted as an inhibitor blocking axonal regrowth and plasticity after CNS (Central Nervous System) injuries [31, 32]. In the present study, a network pharmacology approach was employed to identify the active ingredients of AR-RAS and potential targets when it is utilized to treat TBI.…”
Section: Introductionmentioning
confidence: 99%